Analisis Kekuatan Alat Pengaman Valblock Pada Coupler Kereta - ilham satrio utomo; Dadang Sanjaya Atmaja; Henry Widya Prasetya; Firmansyah Fariz Prasaja (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2020)
The purpose of this study was to analyze the stress, displacement, and factor of safety that occurred in the valblock safety device. With the maximum load that occurs at the knuckle is 7473 N. Testing is done using Solidworks simulation software. The material used is AISI 1045 with allowable stress of 450 MPa. The results of the analysis that came out of the simulation were the maximum stress values, displacement, and the factor of safety. The maximum stress results in static conditions that the tool is only able to withstand loads up to 7000 N with a value of 3,540 , and does not exceed the maximum allowable stress limit of the tool, which is 5,300 . The result of the loading is a change in the shape of the stem, namely displacement or deflection. The results obtained from the deflection of 1.3 mm. For the results of the factor of safety, the tool is worth 1.5 at a load of 7000 N so that the valblock safety device is safe to use up to 7000 N loading. Key Words: Coupler, Valblock, Tegangan, Solidwork 2017